Characterizing the Natural History of Acute Radiation Syndrome of the Gastrointestinal Tract: Combining High Mass and Spatial Resolution Using MALDI-FTICR-MSI. Issue 4 (April 2019) - Carter, Claire L.; Hankey, Kim G.; Booth, Catherine; Tudor, Gregory L.; Parker, George A.; Jones, Jace W.; Farese, Ann M.; MacVittie, Thomas J.; Kane, Maureen A.
Abstract : Abstract: The acute radiation syndrome of the gastrointestinal tract has been histologically characterized, but the molecular and functional mechanisms that lead to these cellular alterations remain enigmatic. Mass spectrometry imaging is the only technique that enables the simultaneous detection and cellular or regional localization of hundreds of biomolecules in a single experiment. This current study utilized matrix-assisted laser desorption/ionization mass spectrometry imaging for the molecular characterization of the first natural history study of gastrointestinal acute radiation syndrome in the nonhuman primate. Jejunum samples were collected at days 4, 8, 11, 15, and 21 following 12-Gy partial-body irradiation with 2.5% bone marrow sparing. Mass spectrometry imaging investigations identified alterations in lipid species that further understanding of the functional alterations that occur over time in the different cellular regions of the jejunum following exposure to high doses of irradiation. Alterations in phosphatidylinositol species informed on dysfunctional epithelial cell differentiation and maturation. Differences in glycosphingolipids of the villi epithelium that would influence the absorptive capacity and functional structure of the brush border membrane were detected. Dichotomous alterations in cardiolipins indicated altered structural and functional integrity of mitochondria. Phosphatidylglycerol species, known regulators of toll-like receptors, were detected and localized to regions in the lamina propria that contained distinct immune cell populations. These results provide molecular insight that can inform on injury mechanism in a nonhuman primate model of the acute radiation syndrome of the gastrointestinal tract. Findings may contribute to the identification of therapeutic targets and the development of new medical countermeasures. Abstract : Supplemental digital content is available in the text.